2012
DOI: 10.3109/02713683.2012.722742
|View full text |Cite
|
Sign up to set email alerts
|

Pars Plana Vitrectomy and Silicone Oil Tamponade as a Primary Treatment for Retinal Detachment Caused by Macular Holes in Highly Myopic Eyes: A Risk-Factor Analysis

Abstract: PPV/silicone oil tamponade is a practical choice for treatment of MHRD in high myopia. While RDs occasionally re-occur after silicone oil treatment, these events are limited and can be managed with simple measures. A large MH is a risk factor for recurrent RD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Although silicone oil was introduced in the initial surgery to avoid the need for face-down positioning, 21 it is necessary to remove the silicone oil afterward, and longterm retinal toxicity cannot be ignored. 18,22,23 Increasing the successful rate of retinal attachment and hole closure and decreasing the duration that patients are in a prone position are the main goals of MHRD repair.…”
mentioning
confidence: 99%
“…Although silicone oil was introduced in the initial surgery to avoid the need for face-down positioning, 21 it is necessary to remove the silicone oil afterward, and longterm retinal toxicity cannot be ignored. 18,22,23 Increasing the successful rate of retinal attachment and hole closure and decreasing the duration that patients are in a prone position are the main goals of MHRD repair.…”
mentioning
confidence: 99%
“…Recent studies on RD caused by a MH treated by PPV plus primary silicone oil tamponade with ILM peeling have suggested a high reattachment rate ranging from 85.1 to 100 % [ 15 18 ]. Nishimura et al reported that PPV with ILM peeling and primary silicone oil tamponade without any postoperative position restrictions led to a 92 % retinal reattachment rate after the initial surgery, with a mean duration of silicone oil tamponade of 23.3 months [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study by Nishimura et al [ 17 ], six clinical factors (age, preoperative BCVA, AXL, area of the RD, combined cataract surgery, and the duration of oil tamponade) were assessed, and all these factors were not correlated with MH closure. Xie et al [ 18 ] assessed clinical risk factors associated with initial anatomical success of MHRD treated with primary silicone oil tamponade with or without ILM peeling, and found that MHRD in myopic eyes with smaller MH diameters were significantly associated with higher initial anatomical successes. The most recent study by Arias et al reported that the area of the fundus autofluorescence and AXL were significantly associated with anatomical outcomes [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations